Gender-based violence and its health risks on women in Yaoundé, Cameroon - Georges Nguefack-Tsague; Adidja Amani; Valérie Djouna Dadjie; Donato Koyalta; Debora Nounkeu Carole; Fanny Nadia Dissak-Delon; Fabrice Zobel Lekeumo Cheuyem; Gilles Protais Lekelem Dongmo; Christelle Mbe Anastasie; Justine Laure Menguene Mviena; Odette Kibu; Marie Nicole Ngoufack; et al. (BMC, 2024)
Abstract Introduction Gender-based violence (GBV) is a major public health problem that disproportionately affects women. In Cameroon, as well as other countries worldwide, GBV has immediate effects on women's health, with one in three women experiencing physical or sexual violence from an intimate partner, affecting their physical and reproductive health. The objective of this study was to determine the health risks associated with GBV among women in Yaoundé. Methods A cross-sectional study was conducted in Yaoundé (Cameroon), from August to October 2022. Adverse health outcome included mental disorders, physical trauma, gynaecological trauma, behavioral disorders, and any other disorder. Tests of associations were used to establish relationships between qualitative variables. Associations were further quantified using crude odds ratio (OR) for univariate analysis and adjusted odds ratio (aOR) for multivariate analysis with 95% confidence interval (CI). Independent variables included: Physical violence, Sexual violence, Economic violence, Emotional violence, Age, Number of children, and Marital status. Variables with p-value˂0.05 were considered statistically significant. Results A total of 404 women aged 17 to 67 years were interviewed. Emotional violence was the most commonly reported violence (78.8%), followed by economic violence (56.9%), physical violence (45.8%) and sexual violence (33.7%). The main reasons for violence were jealousy (25.7%), insolence (19.3%) and the refusal to have sexual intercourse (16.3%). The prevalences of adverse health outcomes were physical trauma (90.9%), followed by mental disorders (70,5%), gynaecological trauma (38.4%), behavioral disorders (29.7%), and other (5.5%). Most victims reported at least one of the above-mentioned conditions (80.2%). Women who were victims of any kind of violence had a higher likelihood of experiencing adverse health outcomes: physical violence [OR = 34.9, CI(10.8-112.9), p < 0.001]; sexual violence [OR = 1.5, CI(0.9-2.7), p = 0.11]; economic violence [OR = 2.4, CI(1.4-3.9), p = 0.001]; and emotional violence [OR = 2.9, CI(1.7-4.9), p < 0.001]. Using multiple binary logistic regression, only physical violence [aOR = 15.4, CI(6.7-22.5), p = 0.001] remained highly associated with an increased likelihood of having adverse health outcomes. Conclusion This study underscores the urgent need for comprehensive interventions to address GBV, including improved reporting and documentation of cases, increased awareness among healthcare providers, the establishment of support networks for victims, primary and secondary prevention of GBV. It is essential that the Government of Cameroon, through the Ministries in charge of Health and Women's Empowerment, minimizes the health effects of GBV through early identification, monitoring, and treatment of GBV survivors by providing them with high-quality health care services.